2014
DOI: 10.1007/s11434-014-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

Water balance and migration for maize in an oasis farmland of northwest China

Abstract: Water balance and migration characteristics are vital to the establishment of an efficient irrigation management system. Based on the observed data including microclimate and growing parameters of maize from 2009 to 2012, actual evapotranspiration during the growth period was estimated by a combination of the FAO-56 crop coefficient approach and the Penman-Monteith model; the changes in soil water storage were estimated through the monitored water content at different depths from 0 to 3 m; the water content mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…The actual deep drainage rate can be estimated using methods such as soil water balance, chloride mass balance, and numerical modeling. However, each of the methods has limitations (Healy, 2010; Lin et al, 2013; Wang et al, 2016; Zhao and Zhao, 2014). In this study, we have shown that the HYDRUS‐1D model driven by soil moisture data measured below the root zone could accurately simulate deep drainage under young irrigated croplands in the desert‐oasis ecotone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The actual deep drainage rate can be estimated using methods such as soil water balance, chloride mass balance, and numerical modeling. However, each of the methods has limitations (Healy, 2010; Lin et al, 2013; Wang et al, 2016; Zhao and Zhao, 2014). In this study, we have shown that the HYDRUS‐1D model driven by soil moisture data measured below the root zone could accurately simulate deep drainage under young irrigated croplands in the desert‐oasis ecotone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the soil is generally coarse textured, with low organic matter and weak structure (Zhang et al, 2017, 2018). The deep drainage coefficient (i.e., the ratio of deep drainage to water input) under the irrigated croplands in this region is more than 20% in the growing season (Ji et al, 2007; Zhao and Zhao, 2014). This deep drainage compounds the problem of agricultural water shortage in this and similar arid areas.…”
mentioning
confidence: 99%
See 3 more Smart Citations